Green Campus Management in Islamic Higher Education: Sustainable Development Goals 13 - Dermawan, Oki; Defriyanto, Defriyanto; Irawansyah, Irawansyah; Busmayaril, Busmayaril; Sain, Zohaib Hassan (International Journal of Islamic Studies Higher Education, 2025)
Universitas Islam Negeri Raden Intan Lampung is committed to advancing green campus management as a proactive response to the challenges of increasing pollution and environmental degradation faced in Indonesia. This research investigates the specific initiatives undertaken by Universitas Islam Negeri Raden Intan Lampung in implementing green campus management. Using a qualitative method with a case study approach, data sources were drawn through in-depth interviews with twenty informants consisting of five university administrators, ten lecturers and students, and five operational staff selected by purposive sampling. To strengthen the results of the interviews, the author also collected data from expert opinions and highly reputable journals related to this research in the same context and issue. All data were analyzed using the Miles and Huberman interactive analysis technique. This research found seven aspects of green campus management at Universitas Islam Negeri Raden Intan Lampung that successfully increase the awareness and participation of the academic community in environmental sustainability. These aspects include i) Institutional Management, ii) Policy and Regulation Management, iii) Education and Curriculum Management, iv) Student Participation Management, v) Reward and Motivation Management, vi) Human Resource Management (Cleaning Staff), vii) Cross-Unit Collaboration Management. This approach forms an environmentally friendly campus culture as a whole.